Analisis Peran Aparat Pengawas Intern Pemerintah dan Aparatur Desa dalam Pengelolaan Keuangan Desa Menuju Good Village Governance: Pendekatan Konsep Karmaphala - Gede Suarsana; I Gede Putu Banu Astawa (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This research aims to find out the Karmaphala concept to make APIP and Village Apparatus realize the principles of Good Village Governance related to village financial management in Lemukih village. This research uses a qualitative descriptive method. Data collection techniques by conducting observations, interviews, and documentation. (1) The village financial management planning has been operating very well even though the community was present to voice their aspirations. (2) The implementation of financial management is very good where village officials are ready to make a budget because they are afraid of the results that will be obtained from these activities. (3) Supervision of village financial management has been very well carried out by the inspectorate and the BPD of Lemukih Village where the inspectorate has carried out supervision of the village office's annual report by providing opinions that are in accordance with the circumstances and also the BPD which has supervised the village government in accountability meetings (4) Reporting and the accountability of the village government when financial management has been very good, as evidenced by the absence of cases of embezzlement and so on.